Cost-effectiveness analysis of adebrelimab in combination with chemotherapy for first-line treatment of extensive-stage small cell lung cancer. - Zhiwei Zheng; Huide Zhu; Ling Fang (PLoS ONE)
Objective This study aims to assess the cost-effectiveness of adebrelimab in combination with chemotherapy as a first-line treatment for extensive-stage small cell lung cancer (ES-SCLC) from the Chinese medical perspective. Methods We have designed a partitioned survival model. The model integrates clinical information pertaining to overall survival, progression-free survival, adverse events and cost data. Our primary measure of outcome in this model is quality-adjusted life years (QALY) and the incremental cost-effectiveness ratio (ICER). The model adopted a willingness to pay (WTP) threshold of $40,343.68 per QALY. To account for uncertainty in the model parameters, we conducted sensitivity analyses. Results The total expenditure for the adebrelimab group was $79,549.34, compared to $6,436.80 for the chemotherapy group. The adebrelimab cohort achieved an incremental gain of 1.25 QALY, resulting in an additional cost of $73,112.54. Consequently, the ICER for the adebrelimab group was determined to be $58,490.03 per QALY, surpassing the WTP threshold of $40,343.68 in China. The sensitivity analyses demonstrated the robustness of the findings across various scenarios. Conclusion This cost-effectiveness analysis indicates that adebrelimab plus chemotherapy as a first-line treatment for ES-SCLC was not cost-effective in China with a WTP of $40,343.68.Reducing the cost of adebrelimab promises to improve the cost-effectiveness of this treatment regimen.